ANALISIS PENGARUH ARUS KAS OPERASI, ARUS KAS INVESTASI & LABA AKUNTANSI TERHADAP RETURN SAHAM PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Khaerunnisa Khaerunnisa; Nafisah Nurulrahmatiah (MANAJEMEN DEWANTARA, 2022)
This study aims to determine the effect of operating cash flow, investment cash flow and accounting profit on stock returns in banks listed on the Indonesia Stock Exchange. This research is an associative type with the research instrument in the form of a list of tables consisting of operating cash flow, investment cash flow, net income and share price of PT. Bank Rakyat Indonesia, Tbk, PT. Bank Negara Indonesia, Tbk , PT, State Savings Bank, Tbk and PT. Bank Mandiri, Tbk. The population in this study were all banks listed on the Indonesia Stock Exchange from 2014-2020 as many as 43 companies. The sample used is 4 state-owned banks listed on the IDX in 2014-2020. The sampling technique used is purposive sampling. Data collection techniques in the form of documentation and literature study. The data analysis technique used classical assumption test, multiple linear regression analysis, multiple correlation coefficient, determination test, t test and f test. Simultaneously operating cash flow, investment cash flow and accounting profit together have a significant effect on stock returns in banks listed on the Indonesia Stock Exchange.